An Approach to the Diastereoselective Synthesis of Cyclohexane-1,3-dicarboxamide Derivatives via a Pseudo Five-Component Reaction Based on Diketene - Talaei, Bahareh; Heravi, Majid M.; Oskooie, Hossein A.; Rezvanian, Atieh (Synlett, 2018)
A one-pot pseudo five-component reaction for the synthesis of 2-aryl-4-hydroxy-4-methyl-6-oxo-N1,N3-dialkylcyclohexane-1,3-dicarboxamide derivatives involving different primary amines, various aromatic aldehydes, and diketene in the presence of triethylamine with high yields is achieved.
Keywords: diketene; cyclohexanone; multicomponent reaction; one-pot reaction; diastereoselective synthesis